2020
DOI: 10.1186/s12864-020-6462-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide map of m6A circRNAs identified in a rat model of hypoxia mediated pulmonary hypertension

Abstract: Background Hypoxia mediated pulmonary hypertension (HPH) is a lethal disease and lacks effective therapy. CircRNAs play significant roles in physiological process. Recently, circRNAs are found to be m6A-modified. The abundance of circRNAs was influenced by m6A. Furthermore, the significance of m6A circRNAs has not been elucidated in HPH yet. Here we aim to investigate the transcriptome-wide map of m6A circRNAs in HPH. Results Differentially express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 58 publications
3
48
0
Order By: Relevance
“…Furthermore, the network of circRNA/miRNA/mRNA is also regulated by m 6 A in HPH. CircXpo6 and circTmtc3 are both m 6 A-modified and then down-regulated in HPH 162 .…”
Section: The Interplay Between M 6 a And Other Epimentioning
confidence: 97%
“…Furthermore, the network of circRNA/miRNA/mRNA is also regulated by m 6 A in HPH. CircXpo6 and circTmtc3 are both m 6 A-modified and then down-regulated in HPH 162 .…”
Section: The Interplay Between M 6 a And Other Epimentioning
confidence: 97%
“…m6A facilitates cytoplasmic export of circRNAs, drives circRNA translation, and mediates circRNA degradation. 32 , 33 Previous reviews have summarized the role of m6A modification in the regulation of ncRNA, including the important processes of controlling RNA functions, including processing, stabilization, and transportation, and the crosstalk between RNA m6A-modified and ncRNA in promoting tumor growth and progression. 34
Figure 1 m6A-modifying process on RNAs m6A receives deposition onto RNAs by the m6A writing element, including WTAP, METTL14, METTL3, VIRMA, HAKA1, RBM15/15B, and ZC3H13.
…”
Section: Epigenetic Types Of Ncrna Modificationsmentioning
confidence: 99%
“…In human embryonic stem cells (hESCs) and HeLa cells, Zhou et al (2017) identified 1,404 m6A circRNAs and 987 m6A circRNAs, respectively, and they found that m6A circRNAs were expressed in cell-type-specific methylation patterns. In a rat model of hypoxia mediated pulmonary hypertension (HPH), Su et al (2020) identified 1130 m6A circRNAs in total. In the lens epithelium cells from age-related cataract (ARC), Li et al (2020) identified 4876 m6A peaks within circRNAs.…”
Section: M6a Modification Of Circrna Widely Existed M6a Modification Of Circrnasmentioning
confidence: 99%
“…Although it was not until 2017 that circRNAs were found to be modified by m6A, many studies have shown that m6A modification of circRNAs plays important roles in physiological processes and disease progressions (Figure 3), such as tumors (Chen R. X. et al, 2019;Chen et al, 2021;Li et al, 2021), acute coronary syndrome (Guo et al, 2020), pulmonary hypertension (Su et al, 2020), and age-related cataract (Li et al, 2020). In this section, we focused on the roles of m6A-modified circRNAs in physiological processes and disease progressions.…”
Section: M6a Circrna and Diseasesmentioning
confidence: 99%